Beyond Loyalty: Unleashing Brand Love for Competitive Supremacy - Erica Adriana (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Establishing a strong brand is crucial for firms to achieve a competitive advantage in today's global marketplace. Strong brands, characterized by valuable assets, unique differentiation, and favorable associations, drive profitability and ensure business sustainability. Brand love, representing a deep emotional connection between consumers and brands, has become a key concept in marketing. Marketers employ brand positioning strategies to foster this emotional connection, recognizing its power to enhance customer loyalty, build strong relationships, and create sustainable competitive advantages. This systematic literature review synthesizes existing knowledge on brand love, focusing on strategies and practices that cultivate it as a source of competitive advantage. The review examines the antecedents, drivers, and outcomes of brand love, addressing how companies can leverage digital marketing to foster brand love, and how brand love contributes to a firm's competitive advantage.